2018
DOI: 10.32598/ijt.12.6.564.1
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and Histopathology Effects of Melissa officinalis Aqueous Extract on the Blood and Vital Tissues of Oncorhynchus mykiss Fish

Abstract: Background: This study was conducted to investigate both the genotoxicity effects of M. officinalis aqueous extract on blood cells and the pathologic changes in the renal, cardiac and splenic tissues of Oncorhynchus mykiss. Methods: 300 fish (Oncorhynchus mykiss) were divided randomly into three groups (N=100 each), consisting of group, 1 (control), and groups 2 and 3 (experimental), which received 450 mg/kg and 1350 mg/kg of body weight the aqueous extract of M. officinalis, respectively. The fish were fed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…It is within the normal levels of liver enzymes indicated by [17,8]. [18] mentioned that high densities of fish cause higher concentrations of liver enzymes because of increased liver cell activity resulting from stress conditions caused by high densities [19] concluded that an increase in liver enzyme values above their normal levels gives evidence of an increase in the rates of liver cell damage. [20] stated that any increase in the levels of transaminase enzymes in the blood serum is caused by physiological, pathological, or nutritional conditions that occur during the duration of the experiment and as a result of the process of stress or excessive food intake, causing stress and disruption in the functions and functioning of the liver.…”
Section: Resultsmentioning
confidence: 71%
“…It is within the normal levels of liver enzymes indicated by [17,8]. [18] mentioned that high densities of fish cause higher concentrations of liver enzymes because of increased liver cell activity resulting from stress conditions caused by high densities [19] concluded that an increase in liver enzyme values above their normal levels gives evidence of an increase in the rates of liver cell damage. [20] stated that any increase in the levels of transaminase enzymes in the blood serum is caused by physiological, pathological, or nutritional conditions that occur during the duration of the experiment and as a result of the process of stress or excessive food intake, causing stress and disruption in the functions and functioning of the liver.…”
Section: Resultsmentioning
confidence: 71%
“…This suggests that the organic extracts of M. officinalis are less toxic through the oral route than the essential oil extracts irrespective of the plant parts. In addition, M. officinalis aqueous extract showed to cause genotoxic and histopathologic damage to the liver, kidneys, heart, and spleen if consumed by Oncorhynchus mykiss fish at doses greater than 450 mg/kg [109], while ethanolic extract showed no antigenotoxic/antimutagenic properties in Swiss albinos mice at 100-250 mg/kg [110]. However, the European Commission, the Panel on Additives and Products or Substances used in Animal Feed could not conclude on the safety of the use of a dried aqueous ethanol extract of M. officinalis leaves as a sensory feed additive for all animal species [111].…”
Section: Animal-based Toxicitymentioning
confidence: 99%
“…Τα φυτικά προϊόντα που προέρχονται από φαρμακευτικά φυτά θεωρούνταν ότι δεν έχουν δυσμενή και τοξική δράση (Jafarpour et al, 2018). Όπως όμως έχει αναφερθεί oρισμένα φυτά μπορεί να περιέχουν τοξικά συστατικά, προκαλώντας βλάβη στα κύτταρα και το γονιδίωμα (Kamdem et al, 2013).…”
Section: βλάβη του Dnaunclassified
“…Οι Singh et al (2014) έδειξαν ότι όταν το εκχύλισμα φύλλων του Jatropha gossypifolia εφαρμόζεται σε υψηλές δόσεις παρουσιάζει γενοτοξική δράση. Έχει αποδειχθεί ότι η χορήγηση εκχυλίσματος Melissa officinalis σε υψηλό ποσοστό είχε σημαντική γενοτοξική δράση στα ερυθροκύτταρα της πέστροφας (O. mykiss) (Jafarpour et al, 2018). Επίσης, η από του στόματος χορήγηση του εκχυλίσματος από το φυτό M. officinalis σε υψηλές δόσεις προκάλεσε παθολογικές αλλαγές στο ήπαρ και στους νεφρούς ποντικών (Namjoo et al, 2013).…”
Section: βλάβη του Dnaunclassified